Bipolar Electrode‐based Electrochromic Devices for Analytical Applications – A Review. Issue 2 (22nd June 2021) - Masturah binti Fakhruddin, Siti; Ino, Kosuke; Inoue, Kumi Y.; Nashimoto, Yuji; Shiku, Hitoshi
Abstract: Bipolar electrode‐based (BPE‐based) electrochromic devices have garnered increasing attention in the past decade. These BPE‐based electrochromic devices have been used for analytical health monitoring, point‐of‐care (POC) diagnostics, and chemical sensing. In this review, we highlight recent progress made regarding BPE‐based electrochromic devices constructed for these analytical applications. Various, available electrochromic materials are summarized in the first section, after which the different device types (e. g., paper‐based and self‐powered) are discussed. Biological‐ and chemical‐based analytical demonstrations of these devices are then reviewed. Finally, we conclude this review with a perspective on the future developments of BPE‐based electrochromic devices in analytical applications. Abstract :